Optimization of the Binmas Online System (BOS) Version 2 (V2) Application in the Maintenance of Conducive Kamtibmas through Door to Door System at Karangjati Polsek Ngawi Police - Aflah, Naufal Rofi (Indonesian Journal of Police Studies, 2024)
This research was conducted due to the maintenance of non-conducive public order in the jurisdiction of Karangjati Sector Police. This is indicated by Karangjati Sector Police ranking as the 4th highest in terms of crime cases among Ngawi Police departments, with a trend of increasing cases every year. Bhabinkamtibmas, as the entity responsible for crime prevention, has not been adequately carrying out the Door to Door System. Currently, in the digitalization era, the police have equipped Bhabinkamtibmas with the Binmas Online System v2 application to facilitate their work. The purpose of this research is to describe, identify factors, and understand the community empowerment efforts to optimize the Binmas Online System v2 application in maintaining a conducive public order through the Door to Door System at Karangjati Sector Police, Ngawi Police Resort. This research uses the concepts of optimization, Door to Door System, Bhabinkamtibmas, conducive public order maintenance, Binmas Online System v2 application, and Sector Policing. The theories used in this research are Mass Communication Theory (Harold D. Laswell), Human Resource Theory (Sonny Sumarsono), SWOT Analysis Theory, Management Theory (POAC), and Collaboration Theory (Communication, Coordination, Collaboration). The research method employed is Qualitative Research with a descriptive analysis approach. The research location is Karangjati Sector Police, using primary data sources (interviews, observation, document study), secondary data, and tertiary data, while also using source and technique triangulation to test the validity of the data. The results showed that the implementation of the Door to Door System by Bhabinkamtibmas at Karangjati Sector Police in maintaining conducive public order through the Binmas Online System v2 application is limited to formalities to account for Bhabinkamtibmas' performance, with some Bhabinkamtibmas struggling due to lack of proficiency in using the Binmas Online System v2 application. Furthermore, in the efforts to empower the community, Karangjati Sector Police's Bhabinkamtibmas can do it effectively. This is evidenced by good relations with the community and the presence of a Security Task Force involving the community. In conclusion, Bhabinkamtibmas at Karangjati Sector Police is not fully optimized in implementing the Door to Door System through the Binmas Online System v2 application, and there is still a lack of knowledge about the features available in the application. Keywords: Maintenance of Public Order and Security, Door to Door System, Binmas Online System v2.